RACS2: a framework of a remote autonomous control system for telescope observation and its application - Wang, Zhi-Yue; Zhang, Guang-Yu; Wang, Jian; Geng, Zhe; Zhu, Ze-Yu; Jia, Ming-Hao; Zhang, Qian; Zheng, Zhen-Hao; Ge, Kun; Gu, Jia-Yao; Zhu, Lu-Cheng; Zhang, Hong-Fei (Frontiers in Astronomy and Space Sciences, 2023)
With the increasing demand for astronomical observations, telescope systems are becoming increasingly complex. Thus, the observatory control software needs to be more intelligent. They have to control each instrument inside the observatory, finish the observational tasks autonomously, and report the information to users if needed. We developed a distributed autonomous observatory control framework named the Remote Autonomous Control System 2nd (RACS2) to meet these requirements. Rich features are integrated into the RACS2 framework. The RACS2 is a modular framework, in which each device control software and system services are implemented as different components. Furthermore, RACS2 framework assimilate new techniques, such as a lightweight message and serialization mechanism. RACS2 also has good compatibility with other frameworks or ecosystems such as Python and the EPICS (Experimental Physics and Industrial Control System). The RACS2 framework can communicate with EPICS-based and Python-based software. With the help of these features, key system components like executor, scheduler are developed. The executor component can support sophisticated tasks. Autonomous observation can be achieved by the scheduler component. A set of web-based Graphic User Interfaces (GUI) is designed to help control and manage the framework remotely. Based on the RACS2 framework, we have implemented the Dome A Twins (DATs) telescope’s observation system and the space object observation system. We performed remote autonomous observation and received many data with these systems. The RACS2 framework also has been used in our other projects like camera control system of Wide Field Survey Telescope (WFST) and its observatory control system, and the design can be a useful reference for the development of other frameworks.